Interaction of acetic acid bacteria and lactic acid bacteria in multispecies solid-state fermentation of traditional Chinese cereal vinegar - Xia, Menglei; Zhang, Xiaofeng; Xiao, Yun; Sheng, Qing; Tu, Linna; Chen, Fusheng; Yan, Yufeng; Zheng, Yu; Wang, Min (Frontiers in Microbiology, 2022)
The microbial community plays an important role on the solid-state fermentation (SSF) of Chinese cereal vinegar, where acetic acid bacteria (AAB) and lactic acid bacteria (LAB) are the dominant bacteria. In this study, the top-down (in situ) and bottom-up (in vitro) approaches were employed to reveal the interaction of AAB and LAB in SSF of Shanxi aged vinegar (SAV). The results of high-throughput sequencing indicates that Acetobacter pasteurianus and Lactobacillus helveticus are the predominant species of AAB and LAB, respectively, and they showed negative interrelationship during the fermentation. A. pasteurianus CGMCC 3089 and L. helveticus CGMCC 12062, both of which were isolated from fermentation of SAV, showed no nutritional competition when they were co-cultured in vitro. However, the growth and metabolism of L. helveticus CGMCC 12062 were inhibited during SSF due to the presence of A. pasteurianus CGMCC 3089, indicating an amensalism phenomenon between these two species. The transcriptomic results shows that there are 831 differentially expressed genes (|log2 (Fold Change)|>1 and, p≤0.05) in L. helveticus CGMCC 12062 under co-culture condition comparing to its mono-culture, which are mainly classified into Gene Ontology classification of molecular function, biological process, and cell composition. Of those 831 differentially expressed genes, 202 genes are up-regulated and 629 genes are down-regulated. The down-regulated genes were enriched in KEGG pathways of sugar, amino acid, purine, and pyrimidine metabolism. The transcriptomic results for A. pasteurianus CGMCC 3089 under co-culture condition reveals 529 differentially expressed genes with 393 up-regulated and 136 down-regulated, and the genes within KEGG pathways of sugar, amino acid, purine, and pyrimidine metabolism are up-regulated. Results indicate an amensalism relationship in co-culture of A. pasteurianus and L. helveticus. Therefore, this work gives a whole insight on the interaction between the predominant species in SSF of cereal vinegar from nutrient utilization, endogenous factors inhibition and the regulation of gene transcription.